Frequency of Thrombocytopenia in Malaria and its prognostic significance - Saleh Ahmad; Saeed-ur-Rehman; Qazi Ikramullah; Iqbal Ahmad (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Thrombocytopenia is a common hematological manifestation of malaria, but locally there is limited data on the association of thrombocytopenia degree and malarial species in Pakistan. Therefore, the present study aims to assess the frequency of thrombocytopenia and its severity among patients with malaria. METHODOLOGY: In this prospective cross-sectional study, a total of 120 patients with smear-positive for malaria on microscopy were included. The patient’s complete blood count (CBC) was assessed daily to monitor the platelet counts, and thrombocytopenia was divided into four categories, i.e., mild, moderate, severe, and very severe thrombocytopenia. RESULTS: Out of the total 120 malaria-positive cases, 78(65%) were positive for P. vivax, 32(26.7%) were affected by P. falciparum, and 10(8.3%) patients had mixed infection. Thrombocytopenia developed among 73% of the total patients with malaria; of these, 35.23% developed mild thrombocytopenia, while 31.82%, 23.86%, and 9.09% developed moderate, severe, and very severe thrombocytopenia, respectively. Among those 30(34.0%) infected with P. falciparum, 8(26.7%) developed mild thrombocytopenia, while 8(26.7%) and 14(46.7%) developed moderate to very severe thrombocytopenia. Similarly, most patients with P. vivax 23(39.7%) had mild to moderate 20(34.5%) thrombocytopenia, 15(25.9%) had severe, and only 5.19% had very severe thrombocytopenia p-value=0.141 shows non-significant association. Furthermore, P. vivax group developed complications, while two of the four patients of the P. falciparum group developed cerebral malaria, one developed renal failure, and the last one had pancytopenia. CONCLUSION: In conclusion, thrombocytopenia is frequent among patients with malaria. Moreover, the severity of thrombocytopenia and complications are more evident among those infected with P. falciparum than those with P. vivax.